Analisis Kualitas Website Kabupaten Lamandau Menggunakan Webqual 4.0 - Irmayanti, Ade; Hidayat, Rahmat; Rahmawati, Endah (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
Indonesia has entered an era of technological disruption, one of is the regulation have been made by the Indonesian government to utilize ICT in the integrated field of government (egovernment). A general example of implementin e-government in Indonesia is the creation of a local government website (Regency / City). By utilizing internet technology, the web is used as a place to provide information that can be accessed anytime and anywhere by the public. With this, analyzing the quality of a local government website is very important to be reviewed, so that a good website is created according to the established standards. The purpose of this research is to analyze the quality of the Lamandau government website based on user perceptions, namely the society. Webqual 4.0 is a method to determine the quality of a website based on user perceptions. The webqual 4.0 method consists of three categories, namely usability, information quality, and service interaction quality. These three categories were used as references in making a questionnaire to analyze the quality of the Lamandau government website. Hopefully the results of this research can be used as a consideration for the development of information systems in the local government of Lamandau Regency.